Biology and ecology of Malaysian pen shells - Idris, Mohd Hanafi; Arshad, Aziz (LAP Lambert Academic Publishing, 2014)
Pen shells is a common bivalve living associatedly with seagrass in marine and brackish water. This species regularly sought after by the local people in Malaysia as the daily protein source. Over the past 15 years, intensifies exploitation of pen shells natural stocks has led to a decline in production and now it gazetted as an endanger species in Malaysia. This book provides information regarding biology, ecology and distribution of Malaysia pen shells. It is aimed as technical reference and baseline study for students, researchers, professionals and managers of the fisheries resource management.